How to manage continuous positive airway pressure (CPAP) failure –hybrid surgery and integrated treatment. Issue 3 (June 2020) - Li, Hsueh-Yu; Lee, Li-Ang; Tsai, Ming-Shao; Chen, Ning-Hung; Chuang, Li-Pang; Fang, Taun-Jen; Shen, Shih-Chieh; Cheng, Wen-Nuan
Abstract: Obstructive sleep apnea (OSA) is a prevalent disease, which influences social relations and quality of life with major health impact. The etiology of OSA is multi-factorial involving both anatomical obstruction and physiological collapse of the upper airway during sleep with different proportion in individual patients. Continuous positive airway pressure (CPAP) is the gold standard and first-line treatment for OSA patients. The mechanism of CPAP is acting as air splint to avoid principal pharyngeal collapse during sleep. Consequently, extrapharyngeal collapse and significant pharyngeal obstructions can lower its compliance and lead to its failure. Adequate mask and pressure with thorough survey to eliminate side effects of CPAP from nasal, mask and flow-related problems are the prerequisite to improve CPAP compliance. For CPAP failure patients, multi-dimensional surgery is an alternative and salvage treatment that involves soft tissue surgery, skeletal surgery, and bariatric surgery. OSA patients with craniofacial anomaly are suggested to skeletal surgery. By contrast, OSA patients with pathological obesity are referred to bariatric surgery. Soft tissue surgery targets at the nose, soft palate, lateral pharyngeal wall, tongue and epiglottis that can be implemented by multi-level surgery with hybrid technique (mucosa-preservation, fat-ablation, muscle-suspension, tonsil-excision, cartilage-reconstruction) to maximize surgical outcomes and minimize complications. Some evolution in surgical concept and technique are noteworthy that include mini-invasive septoturbinoplasty, palatal suspension instead of excision, whole tongue treatment, and two-dimensional supraglottoplasty. Postoperative integrated treatment including myofunctional, positional therapy and body weight control reduces relapse of OSA and improves long-term treatment outcomes.